Development of Digital Illustrated Storybooks for A1 French Reading Skills in Basic Reading Comprehension Course - yunilis andika; Ratna; Ninuk Lustyantie (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2026)
The integration of digital technology into foreign language education has increased the demand for innovative instructional materials that support learner engagement and accessibility. However, the availability of digital reading materials specifically designed for beginner-level French learners remains limited, particularly in Indonesian higher education contexts. This study aims to develop and validate digital illustrated storybooks to enhance reading comprehension in the Basic Reading Comprehension course at the French Language Education Program, Universitas Negeri Jakarta. The study employed a Research and Development (R&D) approach using the Lee and Owens (2004) instructional design model. As part of the second year of a multi-year research project, the study focused on product development and expert validation. The developed product, entitled Lire et Découvrir: Histoires Illustrées Numériques pour le Niveau A1, consists of five thematic digital storybooks covering self-introduction, daily routines, city life and directions, family events, and interpersonal relationships. The materials integrate written texts, illustrations, audio narration, and interactive comprehension activities aligned with CEFR A1 descriptors and adapted from Alter Ego+ A1. The product was validated by a content expert and a media expert. The content validation score reached 90%, while the media validation score reached 92%, indicating that the materials were categorized as very valid. The findings suggest that the integration of visual, textual, and auditory elements enhances learner engagement while facilitating vocabulary acquisition and improving reading comprehension. The developed digital storybooks provide an innovative instructional resource for beginner-level French learners and provide a replicable model for technology-enhanced language learning in higher education